Behavior towards shopping at retailers practicing sustainable grocery packaging: The influences of intra-personal and retailer-based contextual factors. (10th January 2021) - Su, Diep Ngoc; Duong, Tien Hanh; Thanh Tran Dinh, My; Nguyen-Phuoc, Duy Q.; Johnson, Lester W.
Abstract: The study constructed an integrated model of behavior towards shopping at retailers practicing sustainable grocery packaging (SGP) from the influences of intra-personal and retailer-based contextual factors. A questionnaire-based survey was employed to collect data from grocery shoppers at modern grocery retailers in a developing Asian country-Vietnam. By using Partial Least Square-Structural Equation Modeling, the proposed model was empirically tested with a sample of 478 respondents. The study found the direct influences of environmental lifestyle and retailers' environmental reputation on shopping behavior concerning sustainable packaging. Two personal factors (environmental knowledge of sustainable packaging and green self-identity) and two marketing stimuli factors (sales promotion and advertisement) had indirect effects on behavior via attitude towards shopping at retailers practicing SGP. The study is the first to provide an understanding of consumer behavior concerning sustainable packaging from both internal and external perspectives. Practical implications are also provided for marketing and management of grocery retailers.